Mortgage Prepayment and Path-Dependent Effects of Monetary Policy - Berger, David; Milbradt, Konstantin; Tourre, Fabrice; Vavra, Joseph (American Economic Review, 2021)
How much ability does the Fed have to stimulate the economy by cutting interest rates? We argue that the presence of substantial debt in fixed-rate, prepayable mortgages means that the ability to stimulate the economy by cutting interest rates depends not just on their current level but also on their previous path. Using a household model of mortgage prepayment matched to detailed loan-level evidence on the relationship between prepayment and rate incentives, we argue that recent interest rate paths will generate substantial headwinds for future monetary stimuli. (JEL E32, E43, E52, E58, G21, G51)